Tenure matters for team cohesion and performance: The moderating role of trust in the coach - Abrantes, A. C. M.; Mach, M.; Ferreira, A. I. (European Sport Management Quarterly, 2022)
Research question: This study examines team performance as a function of team tenure, cohesion and trust in the coach. Specifically, we propose a moderated-mediation model to explain whether it translates into an objective measure of future team performance. Research methods: The study sample consists of 668 players from 73 professional and top amateur basketball league teams in Catalonia, Spain. Data collection consisted of a survey performed during a regular training session held at the beginning of the second part of the season as well as objective and subjective team performance indicators. Results and findings: Our findings suggest that the indirect effect of team tenure on performance through team cohesion is only significant for high and medium levels of cognitive trust in the coach and low levels of affective trust in the coach. Implications: These findings provide evidence that explains trust’s contribution to fostering team dynamics and how team tenure translates into future team performance. The practical implications of this study suggest that simply promoting team cohesion without taking into account the cognitive trust in the coach will not necessarily increase performance. Therefore, coaches and managers must invest in the amount of work they do with team members and their skills in order to ensure team members have high cognitive trust in them.